IEEE Antennas and Propagation Society International Symposium. Transmitting Waves of Progress to the Next Millennium. 2000 Dige 2000
DOI: 10.1109/aps.2000.874864
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a dielectric rod array for a multiple beam reflector antenna

Abstract: INTRODUCTIONAt the Delft University of Technology a new transportable atmospheric radar (TARA) [l], having a sophisticated antenna system, is under construction. The antenna of TARA has multiple beams pointing at different directions (i.e. Oo, 15' in the two orthogonal planes). The beams are switched electronically by means of a parabolic dish fed by a dielectric rod array located in the focal plane.In an earlier paper [2], we have shown that an array consisting of two dielectric rods separated by 0.77h, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…However, this approach leads to excessive computation time since a large number of subdivisions are required due to the rapidly varying integrand near the singularity. Therefore, only a limited number of subdivisions can usually be used and it has been shown that this approach is adequate only for far-field analysis [14]. For near-field analysis, in which the self-term elements of the impedance matrix must be accurately evaluated, one may extract the singularity from the integrand and integrate the remainder numerically [15].…”
Section: ) Special Treatment Of Integration Over Singularitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, this approach leads to excessive computation time since a large number of subdivisions are required due to the rapidly varying integrand near the singularity. Therefore, only a limited number of subdivisions can usually be used and it has been shown that this approach is adequate only for far-field analysis [14]. For near-field analysis, in which the self-term elements of the impedance matrix must be accurately evaluated, one may extract the singularity from the integrand and integrate the remainder numerically [15].…”
Section: ) Special Treatment Of Integration Over Singularitymentioning
confidence: 99%
“…However, such a brute-force approach is inefficient, because the same value of vector and scalar potentials could appear in 3 different pairs of basis functions. To perform a much more efficient computation we use a method similar to that in [10], in which we need to calculate the magnetic vector potential (13) and the electric scalar potential (14) associated with the basis function on patch observed at the centroid of patch , where 1,2,3, , with the number of triangular patches, and the integrals in (13) and (14) are evaluated over the triangular patch of the source.…”
Section: ) Efficient Calculations Of Impedance Matrix Elementsmentioning
confidence: 99%
“…Further progress in understanding mutual coupling has required consideration of the details of the elements and near field interactions. Coupling models are available for waveguide feed elements [28], Vivaldi antennas [29], and dielectric rod antennas [30]. For the case of an interferometric radiometer with small element spacings, a network theory analysis has been performed [31] to include the effects of coupling and amplifier noise.…”
Section: Introductionmentioning
confidence: 99%
“…We found experimentally that without loss of accuracy, one can reduce the number of points in direction depending on the latitude (value of ) and use points instead of points. This reduces the number of directions asymptotically to (2) yielding a nonnegligible gain in efficiency. Fig.…”
Section: A Fmmmentioning
confidence: 99%
“…The diameter of the reflectors is 3 m, or approximately 33 wavelengths. The reflector antennas are fed by an advanced system of especially designed feed arrays, allowing for multiple beams in different directions and electronic beam-switching [2]. Fig.…”
Section: Introductionmentioning
confidence: 99%